Judicial Review of Constitutional Amendments: Comparative Experiences and Their Relevance to Indonesia - Tumuhulawa, Arifin; Nggilu, Novendri Mohmad; Yassine, Chami; Tampubolon, Muhammad Hatta Roma (Faculty of Law, Jambi University, 2025)
Constitutional amendments, while essential to democratic adaptability, increasingly generate a paradox in which the power to amend risks eroding the foundational identity and normative coherence of constitutional orders. In jurisdictions undergoing intensive constitutional change, the absence of effective constraints on amendment power has enabled forms of constitutional transformation that are formally legal yet substantively unconstitutional. This article aims to examine comparative practices of constitutional amendment review and to assess their relevance for the future design of Indonesia’s constitutional system. Employing a historical–comparative approach, the study analyzes how apex and constitutional courts in selected jurisdictions have developed doctrines to limit and review constitutional amendments. This article advances three original contributions. First, it reconceptualizes constitutional amendment review not merely as a technical instrument of judicial control, but as a mechanism for safeguarding constitutional identity and higher-order constitutional norms. Second, it situates Indonesia’s unamendable clause on the unitary state and the philosophical status of Pancasila within the global doctrine of unconstitutional constitutional amendments, demonstrating their latent justiciability. Third, it offers a normative model for empowering the Indonesian Constitutional Court to act as the institutional guardian of constitutional identity, thereby transforming amendment review into a principled framework for preserving constitutional integrity in periods of political and constitutional flux